2022
DOI: 10.3390/rs14143350
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Evaluation of Four Satellite Precipitation Products and Their Hydrologic Applications over the Yarlung Zangbo River

Abstract: Satellite remote sensing precipitation products with high temporal–spatial resolution and large area coverage have great potential in hydrometeorological research. This paper analyzes the performance of four satellite products from 2000 to 2008 in the Yarlung Zangbo River Basin, namely the Tropical Rainfall Measuring Mission (TRMM), Precipitation Estimation from Remotely Sensed Information using Artificial Neural Networks-Climate Data Record (PERSIANN), Climate Hazards Group InfraRed Precipitation with Station… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Monthly and annual data were acquired from the respective platforms for the 2009-2019 period (validation period) and show record failures of less than 10% (Table 1). The data of the satellite rainfall products used are from the Tropical Rainfall Measuring Mission (TRMM) [42], Climate Hazards Group InfraRed Precipitation with Stations (CHIRPS) [17,23], Remotely Sensed Information using Artificial Neural Networks-Climate Data Record (PERSIANN) [43], and Modern-Era Retrospective Analysis for Research and Applications (MERRA-2) [44] (Table 2). TRMM (TRMM 3B42) data provided by the Goddard Earth Sciences Data and Information Services Center have a temporal resolution of 3 h and are available in a spatial resolution of 0.25 • (about 25 km) as of 1 January 1998 to 31 December 2019 [45,46].…”
Section: Acquisition Of Observed Data and Satellite Rainfall Product ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Monthly and annual data were acquired from the respective platforms for the 2009-2019 period (validation period) and show record failures of less than 10% (Table 1). The data of the satellite rainfall products used are from the Tropical Rainfall Measuring Mission (TRMM) [42], Climate Hazards Group InfraRed Precipitation with Stations (CHIRPS) [17,23], Remotely Sensed Information using Artificial Neural Networks-Climate Data Record (PERSIANN) [43], and Modern-Era Retrospective Analysis for Research and Applications (MERRA-2) [44] (Table 2). TRMM (TRMM 3B42) data provided by the Goddard Earth Sciences Data and Information Services Center have a temporal resolution of 3 h and are available in a spatial resolution of 0.25 • (about 25 km) as of 1 January 1998 to 31 December 2019 [45,46].…”
Section: Acquisition Of Observed Data and Satellite Rainfall Product ...mentioning
confidence: 99%
“…For this research, it was also observed that in some months (May to October), the largest d-index values correspond to the highest correlation values. For the Yarlung Zangbo river basin (China) [43], different rainfall data such as TRMM, CHIRPS, CMORPH (Climate Prediction Center Morphing Method), and PERSIANN were highlighted. The results showed that TRMM presents the best performance (d-index), differing from this research.…”
Section: Monthly Scalementioning
confidence: 99%
“…According to those authors, the performance of satellite products considerably improves when adjusted with in situ observations. Ye et al [67] show a tendency to overestimate precipitation in the cold semi-arid climate (Bsk) zone in the southeast of the Qinghai-Tibet plateau. A possible explanation is that the precipitation detected by satellites in arid zones may evaporate before reaching the surface and thus not be recorded by the gauges.…”
Section: Case Study For North Brazil-r5mentioning
confidence: 99%
“…However, other studies raised concerns regarding the performance of hydrological models at ungauged links [47]. With the rapid development of remote sensing, remotely sensed data, including forcing (e.g., precipitation) or underlying surface values (e.g., terrain and vegetation) have widely been applied in the hydrology community and achieved a considerable success [48][49][50][51]. Motivated by the capabilities of remote sensing data and ML in hydrology, the purpose of this paper was to fill the gap when using ML for hydrological model parameter estimation by investigating the routing parameter CS of the XAJ model, namely, the runoff recession coefficient in a stream network.…”
Section: Introductionmentioning
confidence: 99%